Human behavior understanding : 6th International Workshop, HBU 2015 Osaka, Japan, September 8, 2015. Proceedings /: 6th International Workshop, HBU 2015 Osaka, Japan, September 8, 2015. Proceedings. (2015) - Unknown
No abstract available